2014
DOI: 10.1186/1756-0500-7-661
|View full text |Cite
|
Sign up to set email alerts
|

The selection performance of an antibody library displayed on filamentous phage coat proteins p9, p3 and truncated p3

Abstract: BackgroundFilamentous phage display has become an ordinary tool to engineer antibody fragments. Several capsid proteins have been applied for displaying antibodies, of which gene III (p3) protein is used the most followed by experiments with gene IX (p9) protein. Despite the popularity, there are no library scale studies to objectively compare differences in the selection performance of the libraries, when displayed via different capsid proteins.ResultsIn this study, an identical antibody repertoire was displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…However, the most striking observation was the strong dependence on HV display. This is the first report of multivalent antibody pIX display in de novo library selection, explaining why the superior properties of pIX have not been revealed previously16.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, the most striking observation was the strong dependence on HV display. This is the first report of multivalent antibody pIX display in de novo library selection, explaining why the superior properties of pIX have not been revealed previously16.…”
Section: Discussionmentioning
confidence: 79%
“…Early studies showed that an N -terminal GST fusion prevented pIX display, as pIX was found aggregated in the cytosol of the E. coli host14. Therefore, ompA and pelB signal sequences were added with the aim to facilitate antibody display15, but later reports are conflicting with respect to how well such pIX display performs in comparison to display on pIII91617. We have developed a display system, where pIX is used as display capsid without addition of a signal sequence to the fusion protein1819.…”
mentioning
confidence: 99%
“…ScFv molecules are expressed at the bacteriophage tip as a fusion with the pIII minor capsid protein, [141] typically resulting in libraries of up to 10 10 phage-displayed antibody fragments which can be screened on immobilized antigens to isolate binding partners. [142] Repetitive cycles of this selection and infection of E. coli cells to amplify phages (and generate increased antibody diversity for the next round) can yield high affinity, highly specific binders in 2-4 weeks. [140] Antibody libraries can also be displayed on bacterial, yeast or mammalian cells by genetic fusion to a cell surface-anchored …”
Section: Isolation Of Recombinant Antibodiesmentioning
confidence: 99%
“…Among the five coat proteins of filamentous M13, f1, or fd bacteriophage, the p3 and p8 proteins are the most frequently used carriers in the phage display technology [ 13 ]. The bacteriophage p3 protein is exploited for the N-terminus or, less frequently, for the C-terminus fusion with the peptide, scFv or cDNA libraries [ 14 , 15 , 16 , 17 ]. The fusion with the p8 protein, in contrast to the p3 protein, makes it possible to present thousands copies of ligands on a single phage particle.…”
Section: Introductionmentioning
confidence: 99%